Prevention and disinfection in COVID-19 - Farhan Shaikh (Wolters Kluwer Medknow Publications, 2020)
The global pandemic involving severe acute respiratory syndrome - coronavirus-2 has tested the capacities of the best of the health-care system worldwide. We are in the middle of the pandemic and the knowledge and science regarding the prevention and treatment of this disease is evolving every minute. This review is an attempt to summarize and simplify the knowledge about preventive and personal protective aspects of management of covid-19 infection. It encompasses the approach to infection prevention and personal protection from the admission of patient to the management in the intensive care units.